Medicine and hygiene in the works of Flavius Josephus - Kottek, Samuel S. (Studies in Ancient Medicine, 1994)
This volume deals with the medical and paramedical topics, compiled from the works of Flavius Josephus, the Jewish historian who lived in the first century C.E. in Judea, and later in Rome. The study of medicine from ancient Jewish sources has focused on the Bible and the Talmud, the content of which is primarily theological and cultural. The present work reveals two main trends. Josephus' paraphrase of the Biblical narrative introduced a number of additions and/or discrepancies which bear on medicine. Moreover, his account of the Jewish War and of contemporary political events includes many details related to medicine and hygiene. This book deals with physicians and healers, diseases and epidemics, with surgery, psychiatry and psychology, and with therapeutics. The work concludes with a discussion of medical metaphors and with a sequence of detailed treatments of topics including suicide, the Essenes and King Herod. It throws light on an aspect of Josephus studies which has rarely been considered till now.